A Meaningful Learning Framework for Autistic Students: Teacher Innovation in Elementary - Dewi, Rachmawati Octavia Kusuma; Minsih, (Jurnal Paedagogy, 2026)
This study aims to describe the implementation of Meaningful Learning in an inclusive elementary school and to analyze its impact on students’ learning outcomes. The study employed a qualitative approach using a case study design conducted at SDN Pajang 1 Surakarta. The participants consisted of one classroom teacher, one special education teacher (GPK), and one autistic student. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that Meaningful Learning was implemented through the use of concrete and visual media, experience-based learning activities, adapted student worksheets and evaluation methods, and flexible support tailored to the emotional conditions of the autistic student. Teachers connected learning materials to students’ daily lives, enabling abstract concepts to be understood through real-life experiences. Collaboration between the classroom teacher and the special education teacher further strengthened student understanding through simplified materials and individualized guidance. The implementation of Meaningful Learning positively influenced the student’s conceptual understanding, learning focus, classroom engagement, emotional stability, and motivation. These findings suggest that Meaningful Learning not only enhances the academic development of autistic students but also provides practical implications for inclusive elementary education, particularly in designing adaptive instruction and strengthening collaborative teaching practices.